Efeitos agudos das feniletilaminas sobre a motilidade gastrintestinal em ratos - Oliveira, Daniel Maia Nogueira de (2021)
Phenylethylamines are a broad and diverse class of compounds that include neurotransmitters, hormones, stimulants, hallucinogens, anorectics, bronchodilators, and antidepressants. Many of these compounds are present in dietary supplements with the aim of improving physical fitness and weight loss. The gastrointestinal tract is the first organ system exposed to these compounds after oral ingestion and little is known about their physiological effects on these organs. Thus, the aim of the present work was to study the effects of the following phenylethylamines: β-phenylethylamine (β-PEA), octopamine, 1-4-methylphenylethylamine (1-4-MPEA), 2-methoxy-1-phenylethylamine (2-M-PEA), 1-methyl-1-phenylethylamine (1-M-1-PEA) and β-methylphenylethylamine (β-MPEA) in the motor aspects of the gastrointestinal tract of rats. For this, male Wistar rats weighing 250 – 300 g were used. To assess the contractility of isolated gastrointestinal tract tissues we tested the stomach fundus, proximal, medial and distal small intestine and distal colon tissues. A bath system for isolated tissues connected to force transducers was used to capture isometric contractions. The verification of the effects of phenylethylamines β-MPEA and octopamine on the gastrointestinal motility of liquids was carried out using the dye dilution technique. In tissues of the gastric fundus under resting tone, the phenylethylamines β-PEA, β-MPEA and 1-M-1-PEA presented a contracting response profile. Octopamine, on the other hand, showed a significant relaxing response. In intestinal tissues, 1-M-1-PEA was the only one to present a contracting response in all intestinal tissues. β-PEA and 2-M-PEA and octopamine had a relaxing response in all portions of the small intestine, but octopamine also presented a relaxing response of the colon. All phenylethylamines promoted relaxing effects in carbachol pre-contracted stomach fundus tissues. Such response was also seen in all intestinal tissues, except for 1-M-1-PEA in the distal portion of the colon. Finally, it was demonstrated that β-MPEA and octopamine had distinct effects in tissues of the gastric fundus. The excitatory effects promoted by β-MPEA appear to result from the activation of 5-HT receptors (5A and 6). Its relaxing effect occurred through an as-yet-unidentified pathway. In turn, octopamine only promoted relaxing effects with a probable involvement of 5-HT4 and TA1 receptors. The predominantly inhibitory profile of octopamine was effective in delaying gastrointestinal transit in rats.